Russel Approximation Method And Vogel’s Approximation Method In Solving Transport Problem - Nelly Astuti Hasibuan (The IJICS (International Journal of Informatics and Computer Science), 2017)
Transportation problems can be regarded as one of the problems that occur routinely in a company in the process of distributing products from several sources to certain places. Transportation issues are included in one of the optimization issues in operations research aimed at minimizing transportation costs. Differences in transportation costs can be due to several factors such as distance gap, type of transport used and other things. The optimization of transportation cost can be done by using Vogel Approximation method and Russel Approximation Method. Method. To see the effectiveness of optimization conducted by the two methods is needed a comparison process.